Effect of moisture stress on leaf and root production in cassava (Manihot esculenta Crantz.) - Sreelakshmi, K.; Menon, Meera V. (Journal of Tropical Agriculture, 2019)
Field experiments were conducted at the Agronomy farm of College of Horticulture, Vellanikkara during 2015-16 to assess the effect of moisture stress on leaf production and root yield of cassava varieties grown in different seasons. Four varieties (Vellayani Hraswa, Sree Vijaya, M4 and Sree Athulya) of varying duration were planted in three seasons viz., May, October and December. The results revealed that the highest leaf production, root weight and chlorophyll content were recorded for the crops planted in May and the lowest in December planted crop. Among the varieties, Sree Athulya, the long duration variety, produced significantly higher number of leaves when planted in October and December, whereas the short duration variety, Sree Vijaya, produced higher number of leaves compared to Vellayani Hraswa for both the planting seasons. Root fresh weight was highest for May planting followed by October and December planting. Among the varieties, Sree Athulya and Sree Vijaya recorded higher leaf retention and were observed to be more drought tolerant when moisture stress occurred during early stages of growth.